Naturalne bystrza – ostoje bioróżnorodności: analiza funkcji tarliskowych dla ryb i siedliskowych dla bezkręgowców = Natural riffles – biodiversity havens: analysis of spawning grounds for fish and habitat functions for invertebrates - Bień, Michał. Autor; Plesiński, Karol. Autor (IGiPZ PAN, 2025)
The study presents the results of implementation activities carried out in the Mierzawa riverbed, the aim of which was to recreate the spawning ground for brown trout. The work was preceded by detailed field studies, including hydrodynamic measurements and sampling of bottom sediments, which enabled precise determination of the proper granulation and amount of gravel material needed to rebuild the spawning ground. After the completion of the activities, ecological monitoring was carried out, including further hydrodynamic measurements, analysis of bottom sediments, inventory of spawning nests, ichthyological catches and collection of macrozoobenthos. The studies showed that supplying the riverbed with gravel material resulted in improved hydrodynamic conditions in the spawning ground, which significantly reduced the accumulation of sand in gravel sediments. Hydrodynamic parameters improved, and the bottom sediments contained less sand, favouring better brown trout breeding conditions. As a result, after the work was completed, more spawning nests were noted, and reproductive efficiency was greater. Although the recreated spawning ground was intended for brown trout, other fish species also used it.
24 cm
Keywords: Geography